Ghana’s Digitization Initiatives: A Survey of Citizens Perceptions on the Benefits and Challenges to the Utilization of Digital Governance Services - Demuyakor, John (International Journal of Publication and Social Studies, 2021)
In 2005, Ghana initiated its digital governance strategy, this has resulted in Ghana becoming one of the fastest-growing countries on the African continent noted for flagship initiatives on Government-to-citizens digital systems. However, the have been some concerns from a section of the Ghanaian population about the impacts of these laudable initiatives, especially since 2017. This study aims to investigate citizen's perceptions of digitization initiatives embarked on by the Government of Ghana, in terms of the benefits and challenges of accessing the digital governance services in Ghana. The researcher adopted an online survey questionnaire to collect data from 1, 964 Ghanaians for six months, thus from June 1 2020 to December 1, 2020, on their perceptions of the digital governance initiatives. A total of 1, 964 questionnaires were validly responded to, which translates to 65.4 % of the targeted population for the study. The key finding according to this study revealed that digital governance initiatives in Ghana have greatly help to reduce corruption, increase productivity, and increased citizens e-participation in governance. Despite the key benefits identified by this study, participants also reported challenges such as high-cost internet data and the lack of a legal framework to protect users of digital governance service as key hindrances to digital governance initiatives in Ghana. This study concludes that 68% of citizens see the digital governance services embarked on by the government as beneficial and are easy to use.